Tinjauan Yuridis Peraturan Presiden Nomor: 5 Tahun 2025 tentang Satuan Tugas Penertiban Kawasan Hutan Berhubungan dengan Hak Masyarakat Hukum Adat dan Tanah Milik di Kawasan Hutan - Fakhry Firmanto (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This research critically examines Presidential Regulation Number 5 of 2025 regarding the Forest Area Discipline Task Force and its impact on Indigenous Law Communities and private landholders. Through philosophical, sociological, and juridical lenses, the study analyzes the tension between state-led